Selection of sampling adsorbents and optimisation and validation of a GC-MS/MS method for airborne pesticides. Issue 10 (9th August 2017) - López, Antonio; Coscollà, Clara; Yusà, Vicent
ABSTRACT: A methodology for the sampling and determination of airborne pesticides has been developed. The trapping efficiency of three adsorbents, namely XAD-2, XAD-4 and a sandwich sorbent (PUF-XAD2-PUF), was tested for 34 pesticides and the latter was selected because it presented the highest retention capacity without breakthrough. Pesticides were determined by gas chromatography coupled to an ion trap mass spectrometer in tandem. The method showed recoveries ranging from 70% to 120% with limits of quantification in the range of 16.1–322.6 pg m −3 when 155 m 3 were sampled. This analytical strategy was applied to 10 indoor air samples collected in dwellings from the Valencian Region. Six pesticides, namely diphenylamine, pyrimethanil, bifenthrin, lambda-cyhalothrin, permethrin and cypermethrin were detected in indoor samples with concentrations ranging from 1.46 to 22.02 ng m −3 .